Project Scope and Project Performance: The Effect of Parts Strategy and Supplier Involvement on Product Development - Clark, Kim B. (Management Science, 1989)
This paper examines the effect on product development of project scope: the extent to which a new product is based on unique parts developed in-house. Using data from a larger study of product development in the world auto industry, the paper presents evidence on the impact of scope on lead time and engineering productivity. Studies of the automotive supplier industry suggest that very different structures and relationships exist in Japan, the U.S., and Europe. Yet there has been little study of the impact of these differences on development performance. Further, little is known about the effects of different parts strategies (i.e. unique versus common or carryover parts) on development. The evidence presented here suggests that project scope differs significantly in the industry, even for comparable products. These differences in strategy, in turn, explain an important part of differences in performance. In particular, it appears that a distinctive approach to scope among Japanese firms—high levels of unique parts, intensive supplier involvement in engineering—accounts for a significant fraction of their advantage in lead time and cost.